Costs of globalization - Farrukh Nawaz Kayani; Zhao Zhongxiu; M. Tahir Ali Shah; Umar Nawaz Kayani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
Globalization has both costs and benefits. In this paper we would focus upon one of the damages of globalization to China. It is said that inward FDI replaces local domestic capabilities in import-substitution countries. In the case of China the Chinese domestic industries are lacking technological innovations because of heavy reliance upon FDI. Most of the Chinese exports of electronics are carried under FDI whereas in Korea and Japan they are indigenously-driven. In 1960s, Korea received foreign capital in the form of loans but it denied the entrance to foreign firms. Korea followed the Japanese model by quickly mastering the foreign technology rather than letting foreign firms to establish local subsidiaries and to decide the speed and scope of technology diffusion. Korea and Japan adopted the techno-nationalist policies for attaining autonomous domestic innovated industries. By restricting FDI, Korea and Japan were able to maintain their management independent of Multi-National Companies. In this paper we would try to analyze that whether China's policy of reliance upon FDI is a success or a debacle by comparing it with Korea and Japan.
Keywords: 330; Human capital investments; Returns to education; Sheepskin effects; China; Globalisierung; Soziale Kosten; Humankapital; Bildungsinvestition; Bildungsertrag; China